INFLUENCE OF GENDER, WORK ENVIRONMENT, LENGTH OF SERVICE AND AGE OF ACADEMIC STAFF ON ATTITUDE TO WORK - Yusuf, Folashade N; Omolayo, Benjamin O; Azikiwe, Judith C (PEOPLE: International Journal of Social Sciences, 2016)
Workers attitude to work is a thing of concern to all management of organization. The present study investigated the influence of four socio-demographic variables (gender, work environment, length of service and age) on attitude to work of academic staff in two universities. The study employed an ex-post facto research design using accidental sample to select 100 participants for the study. Questionnaire on the attitude to work self report was used as an instrument to collect data and response from the participants. Four hypotheses were tested in this study and data collected were analyzed using independent t-test and one-way Analysis of Variance (ANOVA). Results showed that socio-demographic variables have no significant influence on attitude to work. Findings were discussed in line with the existing literatures. Based on findings, it is concluded that socio-demographic variables are important in attitude to work of academic workers.